Electroreduction of oxygen on Pd catalysts supported on Ti-modified carbon - Bae, Sung Jong; Nahm, Kee Suk; Kim, Pil (Current applied physics, 2012)
Carbon supports modified with well dispersed anatase TiO2 (C–Ti-X; X (0.25, 0.5, 0.75, and 1.0) represents mass ratio of Ti precursor to carbon) were synthesized with various Ti loadings and used to support Pd catalysts for oxygen reduction. The anatase nanoparticles increased in size with increasing Ti loading. Pd dispersion improved with increasing Ti loading up to the C–Ti-0.75, which resulted in the best catalytic activity. Although the Pd dispersion was lowest on the C–Ti-1.0, it showed better catalytic performance than the catalysts supported on C–Ti-0.25 and C–Ti-0.5. At 0.8V (vs. RHE), the best catalytic activity achieved was respectively 2.7 and 2.7 times the mass and specific activities of Pd supported on un-modified carbon. The interaction between Pd and highly dispersed TiO2 is believed to improve the catalytic activity of Pd supported on TiO2-modified carbons. ► TiO2-modified carbon as support of Pd for oxygen reduction reaction. ► Different Pd dispersion depending on Ti contents. ► Positive effect of interaction between Pd and TiO2 on oxygen reduction.